2006
DOI: 10.1007/s11136-005-3689-7
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life, Depression and Anxiety in Thyroid Cancer Patients

Abstract: HRQL is severely impaired in DTC patients under short-term hypothyroidism. As potential predictors of generic HRQL impairment, depression, anxiety, and mood disturbance could be used to preselect the patients most needing psychiatric care. The high frequency of anxiety should be considered in the aftercare of thyroid cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 29 publications
6
75
3
6
Order By: Relevance
“…Hypothyroidism is associated with a high prevalence of clinical symptoms, such as neuromuscular dysfunction, paresthesia, fatigue, dry skin and cold intolerance [21] . Furthermore, psychiatric disturbances like anxiety and depression [22] also have been described [16,[23][24][25] . Bianchi et al [16] related that the presence of fatigue and psychiatric disturbances was negatively associated with quality of life scores in patients with overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypothyroidism is associated with a high prevalence of clinical symptoms, such as neuromuscular dysfunction, paresthesia, fatigue, dry skin and cold intolerance [21] . Furthermore, psychiatric disturbances like anxiety and depression [22] also have been described [16,[23][24][25] . Bianchi et al [16] related that the presence of fatigue and psychiatric disturbances was negatively associated with quality of life scores in patients with overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Gerding et al [23] and Ljunggren et al [24] noted a relation between less favorable health status scores and the presence of clinical signs in patients with hyperthyroidism. Tagay et al [25] examined the health status in differentiated thyroid cancer patients under short-term hypothyroidism and observed that it was severely impaired in this population (in comparison to the general population). Also, health status was correlated significantly with worse scores in the scale of signs and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A associação entre qualidade de vida, ansiedade e depressão em pacientes com câncer (Jorngarden, Mattsson & Von Essen, 2007;Mystakidou, Tsilika, Parpa, Katsouda, Galanos & Vlahos, 2005;Tagay et al, 2006), e entre qualidade de vida e sexualidade (Fobair, Stewart, Chang, D'onofrio, Banks, Bloom, 2006;Frumovitz et al, 2005;Huget et. al, 2009) foi demonstrada na literatura internacional, porém até então, não foram encontrados dados relacionando todos esses aspectos na literatura latinoamericana.…”
Section: Tabla 2 Resultados Descritivos Do Instrumento De Qualidade unclassified
“…Moreover, socioeconomic burdens including sick leave from work, as well as physical suffering, are markedly increased in all patients undergoing this procedure for thyroid cancer management [12]. To make things worse, some patients experiencing acute short-term hypothyroid symptoms after THW also experience major psychiatric derangements, such as depression or anxiety, and the severity of the disease is comparable to that of patients with major depression requiring regular treatment [11,13]. …”
Section: Discussionmentioning
confidence: 99%